GENETIC DIVERSITY OF Dendrocalamus asper IN JAVA REVEALED BY RAPD MARKERS - Anto Rimbawanto (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2006)
Dendracalamusasper is one of the most widely use and widely distributed bamboo species in Indonesia. A genetic conservation plot has been established to maintain genetic diversity of the species. A total of 115 samples were collected from 12 sites throughout Java. Genetic diversity was revealed using 31 RAPD primers producing 64 polymorphic bands. A total of 81 different multi-locus genotypes (genets) were identified between 115 samples. TI1e total number of multi-locus genotypes in all populations ranged from 3 to 9 (mean 6.5), indicating that all populations consisted of multiple genotypes. Mean genetic diversity was 0.04, (ranging from the lowest 0.009 in Kuningan population to the highest 0.144 in Purwokerto population). The Simpson's diversity index indicated that the most population composed of unique genotype. Geographical differences did not correlate with genetic cluster.